Analysis Of Liquidity, Activity, Solvency and Market Ratio to Assess PT's Financial Performance Matahari Store Department Tbk Year 2018-2023 - Nanci Parsaulian Simamora; Nina Andriany Nasution (Universitas Kristen Indonesia Toraja, 2024)
The aim of this research is to analyze Liquidity Ratios, Activity, Solvency and Market Ratios to Assess the Financial Performance of PT. Matahari Department Store Tbk 2018-2023. The method used in this research is a quantitative descriptive method, the data in this research uses secondary data. Based on the research results, it shows that the Liquidity Ratio and Cash Ratio, the Financial Performance of PT. Matahari Department Store Tbk in 2018, 2019 and 2021 is considered good. Activity Ratio to Receivables Turnover Ratio, Financial Performance of PT. Matahari Department Store Tbk for 2018-2023 is classified as very good. Solvency Ratio with Long Term Dept to Equity Ratio, Financial Performance of PT. Matahari Department Store Tbk in 2018-2019 was classified as very good. Market Ratio with Price Earning Ratio (PER), Financial Performance of PT. Matahari Department Store Tbk in 2018 is classified as very good and Price to Book Value (PBV) in 2018, 2021-2023 is classified as very good.